MENGATASI LEARNED HELPLESSNESS PADA SISWA TINGGAL KELAS MELALUI KONSELING RASIONAL EMOTIF TEKNIK HOMEWORK ASSIGNMENTS - Aulia, Riski (Universitas Negeri Semarang, 2012)
This study aims to determine the efforts and success in overcoming learned helplessness behavior in students failing grades through rational emotive counseling techniques homework assignments. Type of study used is action research. The subjects studied are two repetition students who experienced learned helplessness. Data collection methods used were interviews, observation and documentation. While the data analysis using qualitative analysis.The results of the study showed that after given counseling in the action cycles 1 and 2, showed that the client’s learned helplessness criteria is very low with a decreased percentage. It was concluded that the learned helplessness in repetition students can be solve by using rational emotive counseling with homework assignments technique.